Using R&D cooperative arrangements to leverage managerial experience: A study of technology-intensive new ventures - McGee, Jeffrey E.; Dowling, Michael J. (Journal of Business Venturing, 1994)
During the past decade, increasing attention has been given to the widespread use of research and development (R&D) strategic alliances and cooperative interorganizational relationships. This research has addressed a variety of inter-firm relationships ranging from joint ventures to informal networking. However, most of this literature is based on research involving large established firms. More recently, researchers have recognized that small firms or new ventures are also adopting cooperative R&D strategies with increasing frequency. A variety of reasons for the increasing use of R&D cooperative arrangements in new ventures has been offered, including the need to complement a new venture's existing internal resources, the need to quickly gain the technical capabilities to compete in rapidly changing markets, and the desire to minimize the fixed costs associated with acquiring capital assets. This paper reports the results of a study of new high-technology ventures that examined the relationship between performance, the experience of a venture's management team, and its use of R&D cooperative arrangements. The central proposition of this research was that the effectiveness of R&D cooperative activities is associated with the level of combined expertise possessed by the new venture's management team. Specifically, it was anticipated that new ventures with management teams possessing more experience with the industry and/or with similar technologies would be better able to successfully engage in R&D cooperative activities. The primary data analysis technique was moderated regression. The data was collected from Security and Exchange Commission initial public offering registration statements and other archival documents filed by 210 new ventures in three high-technology manufacturing industries. The results of the regression analysis revealed that sales growth was associated with the use of R&D cooperative arrangements. More important, the results also indicated that this relationship was positive when the new venture's management team was relatively more familiar with the industry, markets, and/or with similar technologies. In other words, our results indicate that the relatively more experienced managers were more proficient at using R&D cooperative activities to strategically position their respective firms vis-à-vis their less experienced counterparts. Evidently, these managers were better able to identify the risks and benefits of engaging in such cooperative activities. Additionally, we provide preliminary evidence that the greater knowledge possessed by the management teams may have allowed the new ventures to reduce the costs associated with R&D market transactions. These findings are important because they suggest that prior managerial experience in similar industries and/or with similar technologies is an important prerequisite for the successful use of R&D cooperative arrangements by new high-technology ventures. Management's knowledge of customer needs, product characteristics, and/or the specific idiosyncracies of the industry and/or technology seems to significantly enhance a new technology-intensive venture's ability to effectively engage in R&D cooperative activities.